Democracy and political culture in the contextualization of the lobby - Oliver-González, Ana Belén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Political culture is the set of attitudes, beliefs and values ​​shared by citizens regarding politics and institutions, plays a crucial role in the functioning and regulation of lobbying in democratic regimes. This study analyze how political culture influences the functioning and regulation of lobbying in democratic regimes, with the aim of identifying practices that promote transparency, representativeness and equity in decision-making processes. Accountability is essential to prevent corruption, increase transparency, improve efficiency, strengthen democracy, ensure accountability, foster innovation, and promote justice and equity in public administration.